2022
DOI: 10.1093/cjres/rsac001
|View full text |Cite
|
Sign up to set email alerts
|

Navigating through the storm: conservancies as local institutions for regional resilience in Zambezi, Namibia

Abstract: The COVID-19 pandemic has disrupted global production networks and challenged the resilience of regional economies to external shocks. The tourism sector was severely affected by the travel bans imposed, as were regions characterised by tourism development, such as Zambezi in northern Namibia. Nonetheless, with the support of the national government, conservancies, as local governance institutions, partly maintained the distribution of value from tourism throughout the pandemic and strengthened agriculture-tou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…The region also experiences prolonged droughts and increased temperatures, especially during the dry season. The local economy is therefore characterized by high unemployment rates (Hulke et al, 2022). To cushion people against poverty and food insecurity, the Namibian government is running a safety net program, including cash transfers for old people, parents with children, and families severely affected by drought or flood.…”
Section: Namibiamentioning
confidence: 99%
See 1 more Smart Citation
“…The region also experiences prolonged droughts and increased temperatures, especially during the dry season. The local economy is therefore characterized by high unemployment rates (Hulke et al, 2022). To cushion people against poverty and food insecurity, the Namibian government is running a safety net program, including cash transfers for old people, parents with children, and families severely affected by drought or flood.…”
Section: Namibiamentioning
confidence: 99%
“…As explained, in Namibia many households receive government transfers. In addition, transfers from NGOs to compensate households for wildlife-caused losses of crops and livestock are common (Hulke et al, 2022).…”
Section: Household Participation In Different Income Sourcesmentioning
confidence: 99%
“…Overall, the authors argue that ICCM offers a different way of thinking for regions that have long been exposed to the influence of globalisation, and that it increases the agency of local actors who are part of GPNs. Sharing Gong et al's (2022a) interest in local institutions adapting in times of crisis, the piece by Hulke et al (2022) looks at how tourism regions like Zambezi in Namibia were able to partly mitigate the disruption of value from tourism throughout the Covid-19 pandemic and strengthened agriculture-tourism linkages to achieve long-term transformation. The authors showed the role of local institutions in constituting a synergetic relationship between adaptation and adaptability through value distribution and capture from GPNs.…”
Section: Contributions To the Special Issuementioning
confidence: 99%
“…Second, several papers focus on regional institutional reactions and firm strategies in response to the four key forces focusing on agency: articles by Bridge and Dodge, (2022) Fu and Cheng (2022), Gong et al (2022a), Kamakura (2022), Hulke et al (2022) and Wolfe et al (2022) give insightful illustrations on how such challenges have been approached, can be leveraged and manoeuvred by different regional or national actor groups and thus lead to the reconfiguration of the GVCs/GPNs.…”
Section: Emerging Cross-paper Themesmentioning
confidence: 99%
See 1 more Smart Citation